Feasibility assessment of projects for risk of failure: how feasibility assessment are done for infrastructure projects - Smith, Ronald George (My University, 2019)
Avoiding project failure is a concern within the discipline of project planning and management. Feasibility assessment is a front-end process used in project planning to analyse risks and avoid failure. The aim was to explore how feasibility assessments for large infrastructure development projects are conducted and the extent to which risk of failure is recognised. Literature review established theory and definition of feasibility assessment as applied to projects. Two cases of large scale infrastructure development projects in South Africa were investigated to compare different approaches of how feasibility assessments are conducted. Methodology was a combination of direct observation, interviews and analysis of documents collected from the case studies. The predominant risk factor recognised by expert feasibility assessors in both cases was found to be perception of risk itself. Questions asked of the experts are designed to lead to a confirmation that the project could go ahead. The questions do not necessarily ask opinion on whether the project should go ahead. Comparison of the cases showed that the process of feasibility assessment was driven by each assessing firm’s own interpretation of the purpose and objective of feasibility assessment. Overall, the study confirms that the feasibility assessment process is useful as a way for project managers to recognise risk of failure before deciding to proceed with a project. However, the process depends on each assessor’s own interpretation of the definition of feasibility assessment and its purpose. Further research is suggested into the distinction between the reasons justifying why a feasibility assessment was not done, and the reasons why feasibility assessment was not considered for a project
A study submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Science in Building by research Johannesburg 2019
Keywords: Gautrain (South Africa); Infrastructure (Economics)--South Africa; Project management--South Africa